Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
(2, 13 )
Step-by-step explanation:
6x - 2y = - 14 → (1)
4x - 3y = - 31 → (2)
multiplying (1) by 3 and (2) by - 2 and adding the result will eliminate y
18x - 6y = - 42 → (3)
- 8x + 6y = 62 → (4)
add (3) and (4) term by term to eliminate y
10x + 0 = 20
10x = 20 ( divide both sides by 10 )
x = 2
substitute x = 2 into either of the 2 equations and solve for y
substituting into (1)
6(2) - 2y = - 14
12 - 2y = - 14 ( subtract 12 from both sides )
- 2y = - 26 ( divide both sides by - 2 )
y = 13
solution is (2, 13 )
Analysis in the picture
ANSWER:
[tex]x = \frac{31}{18} \\ y = \frac{11}{3} [/tex]
![View image Strikelisted](https://us-static.z-dn.net/files/dfc/a7afc101c8b64cb9490ddb1b56053f9a.jpg)
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.